Impact of Variable Speed Limits and Shoulder Lane Openings on Traffic Improvement near Merging Zones under Free Flow Condition - Majid, Hirsh (Sulaimani Journal for Pure and Applied Sciences, 2018)
The distribution of traffic flow in the individual lanes of multilane motorways is an important investigation task in traffic engineering because the lane flow-distribution affects directly the capacity of the motorway section under investigation. This work is a data analysis which shows the impact of variable speed limits (VSLs) and dynamic lane (shoulder lane) on traffic improvement by homogenization flow through different lanes of a highway. Moreover, it indicates the main characteristics of lane flow distribution (LFD) on all lanes of traffic at the downstream of an on-ramp on a highway. It is concluded that the VSLs can homogenize traffic flow on all lanes of a carriageway by increasing the flow on underused lanes (i.e. slow lane) and decreasing the flow on overloaded lanes (i.e. median lane). Furthermore, it is shown that dynamic lane (i.e. shoulder lane) management can improve the traffic situation by supporting a portion of the flow (about more than 10%) during the peak periods.
Keywords: Lane flow distribution; Variable speed limit; Traffic homogenization Highway traffic stream characteristics